Analisis Strategi Pemasaran Produk Simpanan Aman Terencana (Simantra) Pada KSPPS BMT Aman Utama Cabang Pengkol Jepara - Elysia Shefie Patricia; Wahidullah; Cahyaning Budi Utami (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the marketing strategy for Planned Safe Savings (SIMANTRA) products at KSPPS BMT Aman Utama Pengkol Branch. The research method used is qualitative research with data collection techniques through direct observation in the field and an interview process with the head of the KSPPS BMT Aman Utama Pengkol Branch. The research results show that KSPPS BMT Aman Utama Pengkol Branch in implementing the marketing strategy for planned safe savings products (SIMANTRA) consists of five steps, namely: Prospecting, Approaching, Presentation, Handling Objection, and Ideal Closing. Apart from these five steps, KSPPS BMT Aman Utama also uses the